Free-Radical Scavenging Activity and Total Phenolic Compounds of Red and Green Poinsettia Leaves (Euphorbia pulcherrima Willd.) from Lombok Island - Muliasari, Handa; Sopiah, Baiq; Yuanita, Emmy; Ningsih, Baiq Nila Sari (UI Scholars Hub, 2023)
To determine the free-radical scavenging activity and total phenolic content of the ethanol extract of Poinsettia leaves (Euphorbia pulcherrima Willd.) from Lombok Island, we used the 1,1-diphenyl-2-picrylhydrazyl method and expressed the total phenolic content as gallic acid equivalent (GAE) per gram of ethanol extract. The results show the strong antioxidant activity (79.77 ppm) of the ethanol extract of red Poinsettia leaves and the moderate antioxidant activity of green Poinsettia leaves (118.350 ppm). The ethanol extracts of red and green Poinsettia leaves possessed an average of 63.276 ± 0.228 and 22.715 ± 0.090 mg GAE/g extract total phenolic contents, respectively. In addition, the ethanol extracts of red and green Poinsettia leaves exhibited moderate and strong free-radical inhibitory activities, respectively. These findings indicate that color affects the antioxidant ability of leaves and their phenolic content.